Study of Void Probability Scaling of Singly Charged Particles Produced in Ultrarelativistic Nuclear Collision in Fractal Scenario - Susmita Bhaduri; Dipak Ghosh (Advances in High Energy Physics)
We study the fractality of void probability distribution measured in S32-Ag/Br interaction at an incident energy of 200 GeV per nucleon. A radically different and rigorous method called Visibility Graph analysis is used. This method is shown to reveal a strong scaling character of void probability distribution in all pseudorapidity regions. The scaling exponent, called the Power of the Scale-Freeness in Visibility Graph (PSVG), a quantitative parameter related to Hurst exponent, is strongly found to be dependent on the rapidity window size.